(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2025)
The effects of global climate change and extreme weather events are threatening Bangladesh’s fish and aquaculture productivity. Given the negative consequences of climate change, both the national and international societies concur that mitigating the effects of climatic unpredictability and change requires the development of weather and climate services. Additionally, if forecasting data is expertly adapted to fish farmers’ requirements, they may be better able to handle and adjust to climatic and climatic-induced stressors. The primary goal of the study was to determine how much fish farmers knew about using flood forecast information regarding fish farming. Three villages in the Union Islampur upazila, which is part of the Jamalpur district, were the sites of the study: Kulkandi, Chinaduli, and North-Bamna. A sample of 95 randomly chosen fish farmers (about 25% of the total population) out of 380 fish farmers provided the data. Focus groups, matrix ranking, and key informant interviews were among the qualitative and quantitative techniques used in the study’s research methodology. In order to collect both quantitative and qualitative data, formal and semi-structured questionnaires were created. The majority of farmers (53.90%) had a medium level of knowledge, followed by high knowledge (31.57%), and poor knowledge (14.74%) about the use of forecast information in fish farming. Therefore, through a variety of interventions, including training, group discussions, demonstrations, and the distribution of printed materials, concerned authorities like the Department of Fisheries (DOF) should provide chances to increase the knowledge of fish farmers. Regression study revealed that farmers’ knowledge regarding using forecast information in fish farming is positively impacted by their level of education, annual earnings from fish farming, organizational participation, and sources of flood forecast information. Therefore, while creating programs and making decisions, legislators, development practitioners, extension specialists, and others should consider these aspects. Int. J. Agril. Res. Innov. Tech. 14(2): 9-19, December 2024